Biological control of fusarium wilt of rock melon using effective microbes - Ahmed, Salha Ibnouf Elmahdi (2015)
The use of effective microbes obtained from the rhizosphere to suppress soil borne plant pathogens has received greater attention in recent decades as an alternative to chemical fungicides. This study was conducted to explore the effects of effective microbes (EMs) from the rhizosphere of rock melon as bio- control agents (BCAs) against Fusarium wilt caused by Fusarium oxysporum f. sp. melonis (Fom). Two EMs namely MKB04 and KB10 were screened from 72 effective bacteria isolated from the rhizosphere soil of rock melon. The isolate MKB04 was identified based on the Biolog system as Bacillus amyloliquefaciens; though the isolate MKB10 was unsuccessfully identified using biolog system due probably to the limitation of the methods used. However, 16S rDNA sequencing for MKB04 and MKB10 isolates was confirmed at 100% of sequence similarity to B. amyloliquefaciens and Alcaligenes faecalis, respectively compared with related bacteria in the GeneBank. The two isolates were proved to be effectious towards Fom in in vitro biocontrol assay and showed different mechanisms of action, as they produced antibiotic substances which prevent the fungal growth up to 92.05 and 93.18% for MKB04 and MKB10 respectively compared with control and spores germination by 100%. Antibiotic substances were produced in the form of volatile as well as non volatile metabolites. Pyrrolopyrazine alkaloid compound was detected on GC/MS for both isolates which displayed significant biological activities against tested fungal pathogens. Furthermore, the two isolates produced hydrolytic enzymes that degrade the fungal cell components; and responded positively invitro for siderophore and HCN, indole acetic acid (IAA) production, and phosphate solubilisation.B. amyloliquefaciens and Alcaligenes faecalis bioformulations act as elicitors in the production of inducible compound associated with induced resistance (Peroxidase (PO), polyphenoloxidase (PPO), total phenol and lignin content); that subsequently enhance tolerance of the rock melon to Fusarium wilt based on parameters such as delay the symptoms onset,reduce disease incidence by (25, 33.33 and 33.33%),disease severity (18.83, 20.71 and 22.45%) for B. amyloliquefaciens and Alcaligensis faecalis as single or in combination respectively; and epidemic rate at 0.007 units day-1.Histological observations revealed that B. amyloliquefaciens and Alcaligensis faecalis were able to colonise and produce massive deposition of new structures and products in the tissues of the rock melon, which were used as a defense mechanism against infection by Fom. Furthermore, the two bioformulations enhanced the vegetative growth as observed by the increased chlorophyll content, dry weight of the root and shoot, shoot height and root length. Fruit fresh weight, firmness, total soluble solid, titratable acidity and ascorbic acid obtained in this study are within the range of quality standard and customer acceptance. Under storage conditions4 and 25οC, the bioformulations performed retaining their viability over a longer period.In vitro and in vivo activities of the bioformulations of B. amyloliquefaciens and Alcaligensis faecalis as single or in combination against Fom of rock melon suggested that the bacterium has the potential to be a promising eco-friendly biocontrol agent for F. oxysporum f. sp. melonis as well as plant growth promoters.